Sexual violence in the workplace and associated health outcomes: a nationwide, cross-sectional analysis of women in Iceland - Svava Dogg Jonsdottir, MAS; Edda Bjork Thordardottir, PhD; Unnur Anna Valdimarsdottir, ProfPhD; Thorhildur Halldorsdottir, PhD; Sigurbjorg Anna Gudnadottir, MSc; Johanna Jakobsdottir, PhD; Harpa Runarsdottir, MSc; Gunnar Tomasson, PhD; Thor Aspelund, ProfPhD; Arna Hauksdottir, ProfPhD (Elsevier, 2024)
Summary: Background: Workplace sexual violence against women is a pressing global issue with scarce knowledge on its health implications. Existing research is largely limited to specific occupations, which calls for comprehensive, population-based studies. This study aimed to examine the associations between self-labelled workplace sexual violence and a variety of health outcomes in a nationally representative sample of Icelandic women aged 18-69 years. Methods: Participants in this cross-sectional study were women in the Stress-And-Gene-Analysis (SAGA) cohort who answered the question regarding workplace sexual violence, defined in our study as encompassing all work sectors, academic settings, and other school environments. Eligible participants were women, aged 18-69 years, residing in Iceland, who spoke Icelandic and were listed in the Icelandic Population Register or had a contact number registered with the online 1819 service. Poisson and binomial regressions were used to assess the associations between workplace sexual violence and validated measures of current mental and physical health outcomes (eg, probable depression, general anxiety, and severe sleep problems). Multiple imputation was performed to account for missing values in the dataset. Findings: The study was conducted from March 1, 2018, to July 1, 2019. Of the 113 814 women deemed eligible for study inclusion, 104 197 were invited to take part in the online survey. Of those invited, 30 403 women completed the survey and were included in the SAGA cohort. Among these participants, 15 812 provided answers to the question regarding exposure to workplace sexual harassment or violence. Exposure to sexual violence was associated with an increased prevalence of probable depression (prevalence ratio [PR] 1·50 [95% CI 1·41-1·60]), general anxiety (PR 1·49 [1·40-1·59]), social phobia (PR 1·62 [1·48-1·78]), self-harm (PR 1·86 [1·53-2·28]), suicidal ideation (PR 1·68 [1·44-1·68]), suicide attempts (PR 1·99 [1·62-2·44]), binge drinking (PR 1·10 [1·01-1·20]), sleep problems (PR 1·41 [1·48-1·91]), physical symptoms (PR 1·59 [1·48-1·70]), and sick leave (PR 1·20 [1·12-1·28]). The prevalence of the health outcomes among those exposed show age-related differences: younger women report anxiety or depression more frequently, while older women report sleep problems after experiencing workplace sexual violence. Interpretation: In this cross-sectional study self-reported experiences of sexual violence in the workplace were associated with several self-reported health outcomes. The findings suggest a need for targeted interventions to promote workplace safety and to mitigate adverse health implications among people who have experienced workplace sexual violence. Future research should explore factors such as the frequency, duration, and relationship dynamics of workplace sexual violence, as well as the effect on different genders and sexual orientations, to deepen our understanding of these experiences and inform effective prevention strategies. Funding: Reykjavík Energy Research Fund, The Icelandic Gender Equality Fund, European Research Council, and Icelandic Center for Research.